Resolving mystery behind autonomous retrogression of low-grade gliomas; a systematic review - Syed Ijlal Ahmed; Syeda Beenish Bareeqa; Syeda Sana Samar; Syed Daniyal Ahmed Jilanee (Journal of the Pakistan Medical Association, 2020)
Abstract Objective: To review evidence-based data on spontaneous retrogression of low-grade gliomas with respect to interval till regression, type of glioma and patient outcome. Method: The systematic review comprised medical literature in English language published from January 1997 to January 2017 on Scopus, PubMed and Google Scholar databases to establish consensus about the possible mechanism of spontaneous regression, the role of therapeutic intervention and failure of management strategies in low-grade gliomas. Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines were followed during the review. Results: Of the 176 articles identified, 73(41.5%) were shortlisted for detailed assessment. Of them, 10(13.7%) were included; 5(50%) case reports and 5(50%) case series. There were 23 cases of spontaneous regression; 15(65.2%) males and 8(34.7%) females. The interval of regression varied from 3 months to 15.5 years, and the most commonly presenting low-grade glioma type was optic pathway glioma 11(47.4%). Conclusion: The phenomenon of regression was most evident in optic pathway glioma. Literature suggested that low-grade gliomas should undergo serial imaging before implying any therapeutic intervention. However, the evidence-based proof, large-scale experimental studies and ethical considerations are still required to standardise this strategy. Key Words: Pilocytic astrocytomas, Desmoplastic infantile ganglioglioma, DIG, Desmoplastic infantile astrocytomas, DIA, Diffuse astrocytoma, Spontaneous regression. Continuous...